Meta-analysis of radical resection rates and margin assessment in pancreatic cancer. Issue 12 (9th September 2015) - Chandrasegaram, M D; Goldstein, D; Simes, J; Gebski, V; Kench, J G; Gill, A J; Samra, J S; Merrett, N D; Richardson, A J; Barbour, A P
Abstract: Background: R0 resection rates (complete tumour removal with negative resection margins) in pancreatic cancer are 70–80 per cent when a 0-mm margin is used, declining to 15–24 per cent with a 1-mm margin. This review evaluated the R0 resection rates according to different margin definitions and techniques. Methods: Three databases (MEDLINE from 1946, PubMed from 1946 and Embase from 1949) were searched to mid-October 2014. The search terms included 'pancreatectomy OR pancreaticoduodenectomy' and 'margin'. A meta-analysis was performed with studies in three groups: group 1, axial slicing technique (minimum 1-mm margin); group 2, other slicing techniques (minimum 1-mm margin); and group 3, studies with minimum 0-mm margin. Results: The R0 rates were 29 (95 per cent c.i. 26 to 32) per cent in group 1 (8 studies; 882 patients) and 49 (47 to 52) per cent in group 2 (6 studies; 1568 patients). The combined R0 rate (groups 1 and 2) was 41 (40 to 43) per cent. The R0 rate in group 3 (7 studies; 1926 patients) with a 0-mm margin was 72 (70 to 74) per cent The survival hazard ratios (R1 resection/R0 resection) revealed a reduction in the risk of death of at least 22 per cent in group 1, 12 per cent in group 2 and 23 per cent in group 3 with an R0 compared with an R1 resection. Local recurrence occurred more frequently with an R1 resection in most studies. Conclusion: Margin clearance definitions affect R0 resection rates in pancreatic cancer surgery. This review collates individual studies providing an estimate of achievable R0 rates, creating a benchmark for future trials. Abstract : Margin clearance definitions affect radical resection rates